Speed of International Expansion: The Mediating Role of Network Resources Mobilisation (2022)
Multinational Enterprises (MNEs) are often under pressure to expand at the highest possible speed in international markets. They therefore embed themselves in networks of alliances where they can access resources in the form of relational assets, information, and learning to facilitate swifter internationalisation whilst circumventing the risks of time-compression diseconomies. Hence, drawing from the network theory of international business and the perspective of structural embeddedness of interorganisational relationships, this study aims to determine the relationship between access to and mobilisation of network resources in relation to the speed of international expansion among MNEs. For this purpose, we assembled a sample of 131 global-reach MNEs from the airline industry and observed their international expansion activities over a 5-year period. Partial-Least-Squares Structural-Equation Modelling (PLS-SEM) was applied to capture the multidimensionality of internationalisation speed, under the commitment-breadth-intensity framework, as well as the multidimensionality of both embeddedness and mobilisation; similarly, we employ Necessary Condition Analysis (NCA) to identify the necessary antecedent variables in our research model. As a result, understanding was gained of the position of each firm within an international alliance network, in terms of how it creates value by obtaining access to resources for international expansion; furthermore, we learned that access is as necessary as mobilisation to increase internationalisation speed, and that, mobilisation is required to mediate the capture of network opportunities. Consequently, the study provided insights for managerial practice: MNEs should pursue centrality in their networks at the same time as planning their resources mobilisation strategies